Management of nutritional and gastrointestinal issues in RASopathies: A narrative review. Issue 4 (14th December 2022) - Onesimo, Roberta; Giorgio, Valentina; Viscogliosi, Germana; Sforza, Elisabetta; Kuczynska, Eliza; Margiotta, Gaia; Iademarco, Mariella; Proli, Francesco; Rigante, Donato; Zampino, Giuseppe; Leoni, Chiara
Abstract: Noonan, Costello, and cardio‐facio‐cutaneous syndrome are neurodevelopmental disorders belonging to the RASopathies, a group of syndromes caused by alterations in the RAS/MAPK pathway. They are characterized by similar clinical features, among which feeding difficulties, growth delay, and gastro‐intestinal disorders are frequent, causing pain and discomfort in patients. Hereby, we describe the main nutritional and gastrointestinal issues reported in individuals with RASopathies, specifically in Noonan syndrome, Noonan syndrome‐related disorders, Costello, and cardio‐facio‐cutaneous syndromes. Fifty percent of children with Noonan syndrome may experience feeding difficulties that usually have a spontaneous resolution by the second year of life, especially associated to genes different than PTPN11 and SOS1 . More severe manifestations often require artificial enteral nutrition in infancy are observed in Costello syndrome, mostly associated to c.34G>A substitution in the HRAS gene. In cardio‐facio‐cutaneous syndrome feeding issues are usually present (90–100% of cases), especially in individuals carrying variants in BRAF, MAP2K1, and MAP2K2 genes, and artificial enteral intervention, even after scholar age, may be required. Moreover, disorders associated with gastrointestinal dysmotility as gastro‐esophageal reflux and constipation are commonly reported in all the above‐mentioned syndromes. Given the impact on growth and on the quality of life of these patients, early evaluation and prompt personalized management plans are fundamental.